2018
DOI: 10.1159/000489063
|View full text |Cite
|
Sign up to set email alerts
|

Eribulin in Heavily Pretreated Metastatic Breast Cancer Patients in the Real World: A Retrospective Study

Abstract: Objectives: The aim of this study was to investigate efficacy and safety of eribulin in heavily pretreated patients with advanced breast cancer (BC) in a real-life setting. Methods: This retrospective monocentric study included patients with HER-2-negative metastatic BC, pretreated with anthracyclines and taxanes, who were referred to the Oncology Department of Spedali Civili of Brescia from May 2012 to April 2017. Patients received the same dose of eribulin as that used in the EMBRACE trial: 1.4 mg/m2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
(29 reference statements)
6
19
0
Order By: Relevance
“…Overall, the results of our study are comparable with those previously reported. Median PFS (134 days, approximately 4.5 months) was comparable with that reported for previous clinical studies (range: approximately 3–5.1 months) [ 15 , 16 , 20 , 24 , 25 ]. We also report a slightly longer median OS (631 days, approximately 21 months) than previous studies (range: 8.8–15.9 months) [ 15 , 16 , 20 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…Overall, the results of our study are comparable with those previously reported. Median PFS (134 days, approximately 4.5 months) was comparable with that reported for previous clinical studies (range: approximately 3–5.1 months) [ 15 , 16 , 20 , 24 , 25 ]. We also report a slightly longer median OS (631 days, approximately 21 months) than previous studies (range: 8.8–15.9 months) [ 15 , 16 , 20 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…Eribulin has anticancer effect against a wide range of cancers (lung, bladder, cervical, esophageal, and head and neck cancer) and overall survival has shown to be significantly improved in locally advanced or metastatic breast cancer . Eribulin is administered intravenously with a dose of 1.4 mg/m 2 on days 1 and 8 of a 21‐day cycle, metabolized mainly by hepatic CYP3A4 enzyme and excreted unchanged mostly through liver and urine. Therefore, dose reduction is required in hepatic and/or renal impairment (up to 0.7 mg/m 2 ).…”
Section: Oncological Use Dose and Neurotoxicitymentioning
confidence: 99%
“…Its analogue, lenalidomide is also routinely used in hematological malignancies. Eribulin is a synthetic analogue of halichondrin B produced by the marine sponge Halichondria okadai and a relatively newer anticancer agent providing promising anticancer effect in metastatic breast cancer …”
Section: Introductionmentioning
confidence: 99%
“…Eribulin is already being used successfully in community settings around the world, including the United States [52,53], Italy [56,70,71], and Japan [58,60,61]. Depending upon the region, eribulin is currently considered a second-or third-line therapy in patients with MBC.…”
Section: Expert Opinionmentioning
confidence: 99%